The Prevalence of Wilson's Disease: An Update. Issue 2 (31st January 2020) - Sandahl, Thomas Damgaard; Laursen, Tea Lund; Munk, Ditte Emilie; Vilstrup, Hendrik; Weiss, Karl Heinz; Ott, Peter
Abstract : Background and Aims: In 1984, Scheinberg and Sternlieb estimated the prevalence of Wilson's disease to be 1:30, 000 based on the limited available data. This suggested a large number of overlooked cases with potentially fatal consequences. The "Scheinberg‐Sternlieb Estimate" is still widely used, although more recent clinical and genetic studies of higher quality are now available. In the present study, we included these data to update the prevalence estimate. Approach and Results: A MEDLINE Ovid, Science Citation Index Expanded, and PubMed systematic search for all relevant studies on the prevalence of Wilson's disease was conducted. In total, 59 studies (50 clinical and 9 population‐based genetic) were included in the final analysis. We identified 4 recent clinical studies based on nationwide databases of high quality, providing prevalence estimates from 1:29, 000 to 1:40, 000. Higher frequency populations do exist because of frequent first‐cousin marriages and/or a higher mutation frequency. When calculating prevalence from the incidence related to number of births, estimates were 1:40, 000‐1:50, 000. Clinical screening studies, including examination for Kayser‐Fleischer rings or ceruloplasmin, did not improve these estimates because of insufficient sample size or selection biases. Population‐based genetic studies in US and UK populations were not in disagreement with the clinically based estimates. At the same time, studies from France and Sardinia suggested that the genetic prevalence may be 3‐4 times higher than the clinical disease prevalence. This raises the question whether the penetrance is indeed 100% as generally assumed. Conclusions: The original prevalence estimate from 1984 of 1:30, 000‐1:50, 000 still appears valid, at least for the United States, Europe, and Asia. In some population‐based studies, the genetic prevalence was 3‐4 times higher than clinically based estimates. The question of penetrance needs further evaluation.